Pelatihan Kepemimpinan Melayani pada Calon Hamba Tuhan - Adriana Madya Marampa; Dina Ramba; Kres Ari Kawalo (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Leadership as an important aspect that influences a person's behavior specifically in the relationship between the leader and the person being led. Servant leadership implied by the pastor as the leader of the congregation through guidance, direction and encouragement given, has an effect on increasing the spirituality of the congregation. The training activity uses a presentation method, starting with the presentation of material to explain various things related to spiritual leadership in moving the organization. The method used is question and answer and sharing with participants about various things related to spiritual leadership. Training Implementation Time The training was carried out online on August 30, 2024. Participants in the Training for Prospective Pastors were 26 people. The participants' understanding and knowledge of servant leadership increased in the sense that the participants' knowledge increased after participating in the training, this was evidenced by the results of interviews with participants, 90% of participants said that their knowledge and insight increased after participating in the training. Participants said they practiced servant leadership so that leadership was successful effectively and efficiently. Thus, this training is said to be successful because it provides increased knowledge and insight to participants about something that participants need in running an organization, namely servant leadership.